Determing the geothermal parameters, that are responsible for the modern geothermal activity at the Dnieper-Donets ba sin and Donbas - Usenko, A.P.; Usenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The calculations of the heat flow at the central part of Dnieper-Donets basin are carried out, and its distribution is compared with that established for the central part of the Donbas. In the Donbas, the zones of the modern hydrothermal activity are displayed in the heat flow anomalies of a large intensity (up to 80-100 mW/m2). In the Dnieper-Donets basin, the heat flow values, do not higher than 50 mW/m2. Geothermal activity manifestations are recorded with the geothermal gradient jump, which happens at depths higher than 4000-5000 m that coincide with the occurrence of hydrocarbon deposits. The upload of the thermal hydrocarbon-sodium water happens there. At the upper part of the section, the geothermal gradient is not higher than 19-20 ºС/km, though the modern geothermal activity is not displayed in significant heat flow splashes.